Anticancer and anti-angiogenic potentials of probiotics and their bioactive metabolites against colorectal cancer and its tumour microenvironment: a narrative review - Mohd Bajuri, Umi Khalsom; Kalavathy, Ramasamy; Siong, Meng Lim (Faculty of Applied Sciences, 2025)
Colorectal cancer (CRC) is one of the leading causes of cancer-related deaths globally. Unfortunately, current cytotoxic chemotherapy and targeted therapy against CRC are compromised by side effects and cancer resistance. This calls for alternative prevention strategies. Given the majority of CRC are sporadic in nature and associated with diet, probiotics(living microorganismsthat when consumed in adequate amount will confer health benefits on the host) and their bioactive metabolites (postbiotics/functional compounds generated during fermentation) are deemed as viable optionsfor chemoprevention against CRC. This narrative review highlights recent scientific evidence of the straindependent (single-/multi-strains) anticancer effects (action on CRC) as well as modulation of gut microbiota and angiogenesis (actions on tumour microenvironment) of probiotics and their bioactive metabolites. This review features the major mechanisms underlying the dual actions of probiotics and their bioactive metabolites against CRC. The anticancer effects of probiotics are related to reduced inflammation, cell apoptosis, suppressed tumour growth and viability, increased anti-oxidant activity and altered gut microbiota. The anti-angiogenic effects of probiotics are manifested through downregulation of pro-angiogenic VEGF and MMP2, MMP9, METTL3-related pathways, increased anti-angiogenic marker, decreased tumour microvascular density, tumour volume and tube formation as well as downregulation of angiogenesis markers. The most widely studied probiotic-derived bioactive metabolites (exopolysaccharides (EPS), macromolecules, short chain fatty acids (SCFA) and catalase) are also effective against CRC. EPS increased cell apoptosis, downregulated AKT-1, mTOR, JAK-1 pathways, inflammatory markers, cell proliferation, viability and tumour growth. Macromolecules increased Z0-1 protein level whilst reduced cell invasion and MMP-9 gene. SCFA induced cell apoptosis and pH-mediated switch between apoptosis and necrosis, whilst reduced cell viability, proliferation and inhibited Wnt-β/ catenin pathway. Catalase decreased hydrogen peroxide level and increased catalase activities. Generally, clinical evidence of probiotics and their bioactive metabolites against CRC remains limited and their strain-dependent effects pose challenges for clinical applications.